Comparison of Complex Traffic Junction Descriptions in Automotive Standard Formats - Krausz, Nikol; Potó, Vivien; Lógó, János Máté; Barsi, Árpád (Periodica Polytechnica Civil Engineering, 2022)
Autonomous and highly automated transportation is very attractive not only for the automotive but also for the mapping industry. In order to exploit the technology, the latest survey solutions are needed, but beyond that, a clear description of the content is a must. Three standards have been selected: (1) used for a long time in navigation systems (NDS), (2) developed for simulation purposes (OpenDRIVE), and (3) designed and proposed for general map data exchange (GDF). In this paper, we present the approach of the three standards, then apply the tools of the standards to a specific sample area, a complex traffic junction, and produce maps in the appropriate formats. The evaluation of the pilot site shows that the difficulty of the exchange standard appears to be a serious obstacle. In the process of applying the navigation standard, the personality of the evaluator (the map maker) is also revealed. In the simulation format, the description of reality is gradually improved by including more and more extra elements.